Birds of the Masai Mara - Kennedy, Adam Scott (WildGuides., 2012)
Birds of the Masai Mara is a remarkably beautiful photographic guide featuring the bird species likely to be encountered by visitors to the popular Masai Mara National Reserve in Kenya. With an eye-catching layout, easy-to-use format, and no-jargon approach, the book contains more than 300 stunning photographs covering over 200 species of birds and is accessible and informative, rather than purely identification-based. A handy, brief introduction provides visitors with background on the habitats of the national park, and the guide's habitat-based approach makes it simple to identify.